The role and factors impacting virtual human resource management capacity to build remote teams' reliability and retention - Depoo, Lucie; Hermida, Aimee (Serbian Journal of Management, 2024)
The paper investigates the impact of virtual human resource management techniques on the effectiveness of remote teams and employee’s retention to the organization.  The paper provides relevant and new information on virtual teams given the transformational impact resulting from the COVID pandemic.  Data was gathered from 323 managers working with virtual teams formed a base for this study across the globe using an anonymous survey. Data was analysed by two-dimensional statistics. The findings revealed that the implementation of the VHRM has led to high productivity, effectiveness   and retention capacity of employees as they learn to adapt to the technological changes. Results demonstrate that adequate effort and resources invested in VHRM, human resource managers can identify and implement work efficient solutions, investing in new technology/tools for virtual teams (48%), improving communications (52%), and offering new upskilling opportunities for employees, that maximize employee output. Based on the results, remote team effectiveness is not directly affected by virtual work and mainly relates to the career possibilities as well as improved communication combined with professional development. Improvement is tied to integration of Artificial Intelligence, which significantly improve efficiency and workflows, awarding performance and supporting growth.
Keywords: Remote work; web-enabled; human resources; management; virtual teams; retention